Protocol paper: Effects of yokukansan on medication‐overuse headache. Issue 3 (21st March 2019) - Mitsufuji, Takashi; Araki, Nobuo; Ito, Yasuo; Miyake, Akifumi; Takeshima, Takao; Iigaya, Miho; Hirata, Koichi; Suzuki, Norihiro; Nakahara, Jin; Terayama, Yasuo; Sakai, Fumihiko; Arai, Hiroyuki; et al.
Abstract: Background: Medication‐overuse headache (MOH) is one of the most common chronic headache disorders and represents a public health problem. Aim: As we have encountered cases of MOH treated effectively using yokukansan, we planned to analyze the effects of yokukansan on MOH in patients with migraine. Methods: To analyze the effects of yokukansan on MOH in patients with migraine, we planned the study using a double‐blind, randomized, and placebo‐controlled trial. Results: We started to register patients from October 2015, enrolling eight patients in 2015, 35 patients in 2016, 19 patients in 2017, and nine patients as of the time of writing in 2018. We have now collected 71 cases, but recruitment to the trial has not been completed. We need to register more cases to reach the desired number of 80. Conclusion: This article presents the protocol for a double‐blind, randomized, and placebo‐controlled trial to collect evidence of the effects of yokukansan on MOH. The final objective of this study is to reduce headache in MOH while maintaining patient quality of life in good condition.